The courts, the church and the constitution : aspects of the disruption of 1843 / Lord Rodger of Earslferry. - Rodger of Earlsferry, Alan, Lord, 1944-2011 (Edinburgh University Press, 2008)
Commissioned by the Clark Foundation for Legal Education, this book is derived from the inaugural Jean Clark Lectures, hosted by the University of Aberdeen in 2007. Across three lectures, the Rt Hon. Lord Rodger of Earlsferry discusses and analyses the legal and constitutional issues arising from the Disruption of the Church of Scotland in 1843, when the majority of leading ministers left the Church of Scotland to set up the Free Church. Lord Rodger takes a fresh look at the series of cases in the Court of Session and the House of Lords between 1837 and 1843 which led to the Disruption, showing how they gave rise to the most important constitutional crisis and challenge to the Courts' authority that had occurred since the 1707 Union. The first lecture traces the development of the crisis and shows how the dominant party in the Church came to see the judges as failing to invoke the safeguards for its independence enshrined in the Treaty of Union, a situation which was portrayed as a war between the Courts and the Church. Lecture two shows how the counsel and judges in the cases had already been active on either side of the struggle within the Church, and traces the judges' reaction to the Church's challenge to their authority. The concluding lecture considers developments after 1843, particularly the background to the famous decision in the Free Church case of 1904. Finally, Lord Rodger shows how essentially the same issue of spiritual independence can arise today, as shown by the Percy case in 2005.